f1=n(n-1)/4・f0
f2=n(n-1)(n-2)/6・f0,n>3
f3=n(n-1)(n-2)^2/24・f0,n>3
n-k=1,2,3が公式通り
fn-k={k(n,k)/(n-k+1)+(n,k)/2^n-k-1}f0
になっているか確かめてみたい.
===================================
[1]n-k=3
f3={(n-3)(n,n-3)/4+(n,n-3)/4}f0
f3={(n-3)(n,3)/4+(n,3)/4}f0
={(n-3)n(n-1)(n-2)/24+n(n-1)(n-2)/24}f0
=n(n-1)(n-2)/24{(n-3)+1}f0
=n(n-1)(n-2)^2/24・f0 (OK)
[2]n-k=2
f3={(n-2)(n,n-2)/3+(n,n-2)/2}f0
f3={(n-2)(n,2)/3+(n,2)/2}f0
={(n-2)n(n-1)/6+n(n-1)/4}f0
=n(n-1)/2{(n-2)/3+1/2}f0
=n(n-1)(2n-1)/12・f0 (NG)
[3]n-k=1
f3={(n-1)(n,n-1)/2+(n,n-1)/1}f0
f3={(n-1)(n,1)/2+(n,1)/1}f0
={(n-1)n/2+n}f0
=n/2{(n-1)+2}f0
=n(n+1)/2・f0 (NG)
===================================
[まとめ]
fn-k={k(n,k)/(n-k+1)+(n,k)/2^n-k-1}f0
が使えるのは,n-k≧3ということになる.これは予想通りであった.
===================================